FACTORS RELATED TO THE INCIDENCE OF LOWER BACK PAIN IN DAILY FIELD WORKERS IN THE MAHATA SERPONG FLATS PROJECT IN 2024 - Adifa Nur Ma'rifah; Nurfadhilah; Dihartawan; Luqman Effendi (Muhammadiyah International Public Health and Medicine Proceeding, 2024)
One musculoskeletal condition is low back pain, which is defined as pain in the lower back that comes from the spine. In 2021, 12,914 people (3.71%) in Indonesia suffered from low back discomfort. The purpose of the study to ascertain the contributing causes to the prevalence of lower back pain among the Mahata Serpong Flats (Rusun) Project's daily field workers. kind of cross-sectional quantitative descriptive study design. Questionnaires, observation techniques, and the Numeric Pain Rating Scale (NPRS) were used to gather data on low back pain. The study's sample consisted of 85 respondents, and the research methodology employs probability sampling with the kind of simple random sampling. The Chi-Square test of research analysis revealed a link. There was no correlation between low back pain and smoking status (p value = 0.068), physical activity (p value = 0.779), or working life (p value = 0.033), age (p value = 0.046), workload (p value = 0.022), or working hours (p value = 0.0003). Low back discomfort is correlated with working years, age, workload, and working hours. It is advised that employees use weight assistance, stretch in between tasks, and engage in frequent, appropriate, quantifiable exercise.